2013
DOI: 10.1007/s11033-013-2629-9
|View full text |Cite
|
Sign up to set email alerts
|

Sequence polymorphisms at the growth hormone GH1/GH2-N and GH2-Z gene copies and their relationship with dairy traits in domestic sheep (Ovis aries)

Abstract: The purpose was to analyze the growth hormone GH1/GH2-N and GH2-Z gene copies and to assess their possible association with milk traits in Sarda sheep. Two hundred multiparous lactating ewes were monitored. The two gene copies were amplified separately and each was used as template for a nested PCR, to investigate single strand conformation polymorphism (SSCP) of the 5'UTR, exon-1, exon-5 and 3'UTR DNA regions. SSCP analysis revealed marked differences in the number of polymorphic patterns between the two gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…The data from ewes that presented evidence of clinical disease or mastitis were excluded from milk sampling. The milk composition (low casein number, lactose and urea content, high pH, and particularly, SCS), when compared with the Sarda sheep in similar farming systems (Mura et al, 2012;Vacca et al, 2013), still suggested that the ewes that produced the NC samples were affected by subclinical mastitis, which is known to negatively affect milk coagulation and cheese yield in ovine species (Merin et al, 2004).…”
Section: Noncoagulating Milk Samplesmentioning
confidence: 99%
“…The data from ewes that presented evidence of clinical disease or mastitis were excluded from milk sampling. The milk composition (low casein number, lactose and urea content, high pH, and particularly, SCS), when compared with the Sarda sheep in similar farming systems (Mura et al, 2012;Vacca et al, 2013), still suggested that the ewes that produced the NC samples were affected by subclinical mastitis, which is known to negatively affect milk coagulation and cheese yield in ovine species (Merin et al, 2004).…”
Section: Noncoagulating Milk Samplesmentioning
confidence: 99%
“…However, this may also have some negative effects. Some literature indicates that the variants led to increased milk components, but reduced the milk yield [46][47][48]. Regrettably, in this study, because of the lack of data on the milk yield of dairy goats, the effect of this indel on this aspect cannot be studied.…”
Section: Discussionmentioning
confidence: 85%
“…The GH of sheep was sequenced by different studies, it was 2,055 and 2,219 bp long for GH1/ GH2-N and GH2-Z in Sarda sheep (Vacca et al, 2013), 2162 bp (Orian et al, 1988) and 1629 bp for Lohi sheep (Gul et al, 2009).…”
Section: Correlations and Regression Analysis Resultsmentioning
confidence: 99%
“…DQ46164. Two were located at the 5\ UTR, two at the 3\ UTR; one was located in exon-5 (G556A) and resulted in a putative amino acid substitution G186S (Vacca et al, 2013). Seven SNPs were detected in a Portuguese sheep breed (Bastos et al, 2001).…”
Section: Correlations and Regression Analysis Resultsmentioning
confidence: 99%